Ligand‐Induced Evolution of Intrinsic Fluorescence and Catalytic Activity from Cobalt Ferrite Nanoparticles. Issue 8 (13th April 2015) - Pal, Monalisa; Kundu, Anirban; Rakshit, Rupali; Mandal, Kalyan
Abstract: To develop CoFe2 O4 as magneto‐fluorescent nanoparticles (NPs) for biomedical applications, it would be advantageous to identify any intrinsic fluorescence of this important magnetic material by simply adjusting the surface chemistry of the NPs themselves. Herein, we demonstrate that intrinsic multicolor fluorescence, covering the whole visible region, can be induced by facile functionalization of CoFe2 O4 NPs with Na‐tartrate. Moreover, the functionalized CoFe2 O4 NPs also show unprecedented catalytic efficiency in the degradation of both biologically and environmentally harmful dyes, pioneering the potential application of these NPs in therapeutics and wastewater treatment. Detailed investigation through various spectroscopic tools unveils the story behind the emergence of this unique optical property of CoFe2 O4 NPs upon functionalization with tartrate ligands. We believe our developed multifunctional CoFe2 O4 NPs hold great promise for advanced biomedical and technological applications. Abstract : I can sing a rainbow: Through the facile surface modification of CoFe2 O4 nanoparticles (NPs) with Na‐tartrate ligands, intrinsic multicolor fluorescence is achieved, covering the whole visible region, ranging from blue, cyan, and green to red. The functionalized NPs show unprecedented catalytic and photocatalytic activity in the degradation of biologically (bilirubin) and environmentally (methylene blue) harmful pigments.